2008
DOI: 10.1021/jf802298w
|View full text |Cite
|
Sign up to set email alerts
|

Oregano: A Source for Peroxisome Proliferator-Activated Receptor γ Antagonists

Abstract: Peroxisome proliferator-activated receptors (PPARs) are drug targets for several perturbations of metabolic syndrome, defined as the coexistence of obesity, hyperglycemia, hypertension, and hyper/dyslipidemia. In this study, PPAR activation by oregano (e.g., Origanum vulgare) and its components was tested. Oregano extracts bind but do not transactivate PPARgamma, and binding affinity differs among different oregano extracts. The extracts contain PPARgamma antagonists (e.g., quercetin, luteolin, rosmarinic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 25 publications
(42 reference statements)
4
49
1
13
Order By: Relevance
“…We found that luteolin exhibits weak partial agonist behavior relative to the full agonist rosiglitazone in cell transactivation assays and that it acts predominantly as an antagonist in gene expression and adipocyte differentiation assays, explaining apparently contradictory results that have suggested that this ligand is an agonist or an antagonist (Mueller et al, 2008;Park et al, 2009;Ding et al, 2010). Our studies also revealed that luteolin exhibits full agonist actions at least one gene in 3T3-L1 cells, GLUT4, and acts as a potent anti-inflammatory agent through PPAR␥ in HCECs.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We found that luteolin exhibits weak partial agonist behavior relative to the full agonist rosiglitazone in cell transactivation assays and that it acts predominantly as an antagonist in gene expression and adipocyte differentiation assays, explaining apparently contradictory results that have suggested that this ligand is an agonist or an antagonist (Mueller et al, 2008;Park et al, 2009;Ding et al, 2010). Our studies also revealed that luteolin exhibits full agonist actions at least one gene in 3T3-L1 cells, GLUT4, and acts as a potent anti-inflammatory agent through PPAR␥ in HCECs.…”
Section: Discussionsupporting
confidence: 51%
“…Among them, luteolin (3Ј,4Ј,5,7-tetrahydroxyflavone), present in celery, green pepper, perilla leaf, and chamomile tea, is a PPAR␥ ligand with antioxidant and anti-inflammatory properties (Xagorari et al, 2001). Different studies, however, have suggested that luteolin can function either as a PPAR␥ agonist [enhances expression of PPAR␥-dependent genes in adipocytes (Ding et al, 2010)] or a PPAR␥ antagonist [inhibits adipogenesis and PPAR␥-dependent gene expression in other contexts (Mueller et al, 2008;Park et al, 2009)]. The fact that the mode of luteolin action is unclear prompted us to determine the mechanism of luteolin interaction with PPAR␥ and the biological relevance of such an effect in inflammatory response in human corneal epithelial cells (HCECs).…”
Section: Introductionmentioning
confidence: 99%
“…Высокая терапевтическая активность ПФК, несомненно, определяется лечебными свойствами его основных компонентов: РК, ЛТ и ДСЛ, биологическая активность и возможные механизмы действия которых рассмотрены ниже. Фенолпропаноид РК, флавон ЛТ и его аналоги обладают выраженной антиоксидантной, противовоспалительной активностью, оказывая модулирующее действие на РАППы, которые являются одними из основных регуляторов липидного и углеводного обмена [5,6,11,12].…”
Section: действие на сигнальные пути рецепторов-активаторов пролифераunclassified
“…Эндогенными лигандами этого рецептора являются свободные жирные кислоты (СЖК), а некоторые экзогенные лиганды используются как лечебные средства для лечения СД2 [12]. Антагонисты РАППg препятствуют ожирению и обладают противодиабетической активностью [13].…”
Section: действие на сигнальные пути рецепторов-активаторов пролифераunclassified
See 1 more Smart Citation